A REVIEW ON THE EFFECT OF CASSAVA PEEL MEAL IN LIVESTOCK PRODUCTION - Obado, Chukwuma Marley; Ade, samson; Irikefe-Ekeke, Peter; Agadama, Oghale Evelyn; Amata, Alex Ifo (FUDMA Journal of Sciences, 2026)
Cassava peels are abundant agro-industrial by-products generated during cassava processing particularly in major producing countries such as Nigeria. Despite its availability, their utilization in livestock feeding is constrained by low protein content, poor digestibility and the presence of anti-nutritional factors such as cyanogenic glycosides and phytate. This review evaluates the potential of cassava peels as an alternative energy source in livestock diets, focusing on its nutritional characteristics, limitations, and methods for improvement. Processing techniques, especially fermentation, have been shown to reduce toxic compounds and enhance nutrient availability. Evidence from various studies indicates that properly processed cassava peels can partially or completely replace conventional feed ingredients like maize in poultry, ruminant, rabbit and swine diets without adverse effects on performance. Their inclusion also contributes to reduced feed costs and improved sustainability through waste utilization. However, further research is therefore required to evaluate long-term safety, particularly the accumulation of residual hydrogen cyanide in animal tissues.
Keywords: Cassava peels; livestock nutrition; Fermentation; Anti-nutritional factors; Feed cost reduction